Odpowiedzi

2010-03-17T16:45:54+01:00
A) 3(x+2)+2(2x-3)=-12+x
3x+6+4x-9=-12+x
3x+4x-x=-12-6+9
6x=-9 |:6
x=-9/6 = 1 i 3/6

b) 1- x-3=2x
-x-2x=-1+3
-3x=2 |:(-3)
x=-2/3

a) 2- x-1=x
-x-x=-2+1
-2x=-1 |:(-2)
x=- 1/2

Chyba źle .. ; / xd
2010-03-17T16:47:59+01:00
A)3(x+2)+2(2x-3)=-12+x
3x+6+4x-6=-12+x
3x+4x-x=-12+6-6
6x=-12 I: 6
x=-2

b) 1- x-3=2x
-x-2x=3-1
-3x=2 I : (-3)
x= -2/3


c) 2- x-1=x
-x-x=1-2
-2x= -1 I : (-2)
x=1/2
2010-03-17T17:24:38+01:00
3(x+2)+2(2x-3)=-12+x
3x+6+4x-6=-12+x
6x=-12 /6
x=-2

1- x-3=2x
-3x=2 /-3
x= -2/3

2- x-1=x
-2x=-1 /-2
x=1/2